Hubungan Bullying dengan Burnout pada Karyawan - Helwan Andriansyah; Alimatus Sahrah (University of Merdeka Malang, 2014)
This study aimed to determine the relationship between bullying burnout experienced by employees. The hypothesis was a positive relationship between bullying with burnout in employees. This means that the higher the tendency of bullying experienced by employees experiencing burnout will be higher, the lower the contrary, the trend of bullying experienced burnout in employees will get low. Subjects were employees of the company Liquid Club engaged in the field of entertainment as much as 40 people. The results of the analysis of the obtained product moment correlation r xy of 0.373 (p 0.01). This suggests a positive relationship between bullying experienced by the employee burnout. Determinant coefficient obtained for r 2 = 0.139 means bullying against burnout variable contribution of 13.9%. Thus the hypothesis that there is a positive relationship between bullying experienced by burnout in employees can be accepted.